Nutritive value of palm oil sludge fermented with Aspergillus niger after therma1 drying process - Purwadaria, T; Sinurat, A.P; ., Supriyati; Hamid, H; Bintang, I.A.K (Indonesian Animal Sciences Society, 1999)
Solid substrate fermentation by Aspergillus niger has been carried out to improve the nutritive value of palm oil sludge (POS). POS was fermented aerobically for four days in a fermentor chambers (28°C, RH 80%), with 60% moisture content Some of the product was further incubated anaerobically for 2 days at 28°C. Both products from aerobic and anaerobic fermentation processes were dried by various methods, i.e. sunlight, oven at 60°C, oven with blower at 40°C, at the moisture content less than 11%. Results of the drying methods were also compared with the fresh fermented product. Statistic analysis using factorial design (2 x 4) showed that there was no interaction between kind of fermentation processes (aerobic and anaerobic) and drying methods (fresh, sunlight, oven 60°C, and blower 40°C) for almost all parameters except total a-amino acid content Significant results (p<0.05) were obtained on the drying methods for parameters of crude protein, true protein, in vitro dry matter and protein digestibilities, and mannanase and cellulase activities. There were no significant results between treatments in the crude fiber analysis and soluble nitrogen content Significant results also did not occur between treatment of aerob and anaerob fermentation processes for almost all parameters except for dry matter digestibilities. Results from true protein and in vitro digestibilities show that the fresh fermented product has the best nutritive value, while product dried by sunlight was best among other drying processes. Results from in vivo of protein and energy digestibilities show that there were better metabolizable energy and protein for product with aerobic process and dried with oven and blower treatments, while sunlight drying was best for product processed in anaerobic condition. Although fresh fermented product gave better result from in vitro digestibilities and enzyme activity analyses, for some reasons (easy handling and preservation) sunlight drying gave best results for products processed under anaerobic condition, especially when sunlight drying is cheap. Key words: Palm oil sludge, fermentation product, Aspergillus niger, thermal drying